Revisiting flow regionalization in the middle paranapanema region in the state of SÃo Paulo: The use of flow duration curves in watersheds - Silva, César de Oliveira Ferreira [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Instituto Geologico, 2020)
The scarcity of information to support decision-making in water resources management is one of the main restrictions to the adequate use of such resources. Flow regionalization, which aims to overcome the lack of measured flow rate data by using hydrological information from other watersheds with similar physical characteristics, has vital importance. The State of São Paulo uses a flow regionalization method that was formulated with data from the 1940s to the 1980s in order to manage water use concession proposals in regions with no historical fluviometric data. The present study assessed the efficiency of this flow regionalization method by checking it against monthly mean flow rate values obtained for five watersheds of the “Middle Paranapanema” Water Resources Management Unit (UGRHI 17), which in turn composes the “Middle Paranapanema” Basin Committee (CBH-MP). The goodness of fit of the flow duration curves derived from flow regionalization data was analyzed, considering: (1) whether this kind of flow duration curves provide enough information for decision making, and (2) what impacts can be generated by the use of such flow regionalization method. The analyses were made for three time frames, using data obtained before and after 1990, and using the complete historical series. This procedure enabled to depict the shortcomings of the flow regionalization model built with outdated data. The underestimation of data was proven by goodness-of-fit tests that yielded the worst results for the smaller watersheds. On the other hand, the flow duration curves yielded better goodness of fit for mean flow rate values obtained before 1990. The main source of uncertainty in maintaining the use of this methodology is its outdated in face of climate change scenarios. When it comes to water use concessions, more restrictive scenarios than the real ones result the use of such flow regionalization model; when it comes to the planning of civil engineering works, the predictability of extreme events, such as floods, is underrated. The methodology can generate impacts on water security (with more restrictive concessions and underrated predictability of floods) and obstacles to sustainability of water use in the watersheds. Advances in the study of flow regionalization, as well as the expansion of hydrometric networks, can broaden the bases for decision making in water resource management in Basin Committees.
Revisitando a regionalizaÇÃo de vazÕes na regiÃo do mÉdio paranapanema no estado de SÃo Paulo: UtilizaÇÃo de curvas de permanÊncia em microbacias hidrogrÁficas
Keywords: Flow duration curve; Historical series; Hydrology; Modeling; Water availability